y=(log x)^cos x + (x^2 + 1)+(x^2 - 1) .find dy/dx

We have,y = log xcos x + x2+1x2-1Let y = u + vwhere u = log xcos x   and  v = x2+1x2-1Now, y = u + vdydx = dudx + dvdx    .....1Let u =  log xcos xlog u = cos x . loglog x1ududx = cos x × 1x log x + loglog x- sin xdudx = ucos xx log x - sin x . loglog xdudx = log xcos xcos xx log x - sin x . loglog xLet v =  x2+1x2-1dvdx = x2-1×ddxx2+1 - x2+1×ddxx2-1x2-12dvdx =x2-1 . 2x - x2+1 . 2xx2-12dvdx =2x3 - 2x - 2x3-2xx2-12dvdx =-4xx2-12Now, from 1, we getdydx = log xcos xcos xx log x - sin x . loglog x-4xx2-12

  • 9
What are you looking for?